2022
DOI: 10.1155/2022/9516029
|View full text |Cite|
|
Sign up to set email alerts
|

Balloon Eustachian Tuboplasty and Grommet Insertion: A Combined Surgical Treatment for Chronic Suppurative Otitis Media with Eustachian Tube Dysfunction

Abstract: Objectives. This study aims to evaluate the effectiveness of Balloon Eustachian tuboplasty (BET) and grommet insertion in patients having chronic suppurative otitis media combined with eustachian tube dysfunction (CSOM-ETD). Methods. We evaluated the data of CSOM-ETD patients (n = 96) from January 2019 to January 2021, who were divided into the following groups: 48 cases underwent BET (BET group) and 48 cases underwent BET plus Grommet insertion (BET + Grommet group). The air-bone gap (ABG), Eustachian Tube Dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A grommet's goal is to make ventilation of the middle ear rather than draining it. Grommets therefore mimic the role of the glue ear's closed eustachian tube and increase hearing (6) .…”
Section: Introductionmentioning
confidence: 99%
“…A grommet's goal is to make ventilation of the middle ear rather than draining it. Grommets therefore mimic the role of the glue ear's closed eustachian tube and increase hearing (6) .…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%